"Oops! I forgot HIV": Resident physician self-audits and universal HIV screening. Issue 2 (March 2015) - Brennan, Meghan B.; Barocas, Joshua A.; Crnich, Christopher J.; Hess, Timothy M.; Kolehmainen, Christine J.; Sosman, James M.; Sethi, Ajay K.
Summary Background Innovations are needed to increase universal HIV screening by primary care providers. One potential intervention is self-audit feedback, which describes the process of a clinician reviewing their own patient charts and reflecting on their performance. Methods The effectiveness of self-audit feedback was investigated using a mixed methods approach. A total of 2111 patient charts were analyzed in a quantitative pre-post intervention study design, where the intervention was providing self-audit feedback to all internal medicine residents at one institution through an annual chart review. Qualitative data generated from the subsequent resident focus group discussions explored the motivation and mechanism for change using a knowledge–attitude–behavior framework. Results The proportion of primary care patients screened for HIV increased from 17.9% (190/1060) to 40.3% (423/1051). The adjusted odds ratio of a patient being screened following resident self-audited feedback was 3.17 (95% CI 2.11, 4.76, p < 0.001). Focus group participants attributed the improved performance to the self-audit feedback. Conclusions Self-audit feedback is a potentially effective intervention for increasing universal HIV screening in primary care. This strategy may be most useful in settings where (1) baseline performance is low, (2) behavioral change is provider-driven, and (3) resident trainees are targeted.